Butterfly Diversity as a Bioindicator of Ecosystem Health at Bukit Doa, Tomohon - Talantan, Puput; Lang, Martina A.; Pollo, Hard N. (Asia Pacific Journal of Interdisciplinary Studies, 2026)
Butterflies (Lepidoptera: Rhopalocera) are a group of insects that are sensitive to habitat changes, making them potential bioindicators of ecosystem health. This study aims to evaluate the structure of butterfly communities in three habitat types—forest, shrubland, and open areas—in the Bukit Doa Mahawu area, Tomohon. Observations were conducted using a 300-meter-long, 10-meter-wide line transect method during two observation periods: March and July 2025. The results showed that 43 butterfly species from four families were recorded, with the highest diversity index (H’ = 3.10) in the forest habitat, while the open area had the highest number of individuals and was dominated by generalist species. Variations in microclimate, vegetation structure, and disturbance levels influenced differences in community composition between habitats. The novelty of this study lies in the provision of baseline data on butterfly communities and their relationship with environmental factors and disturbance levels as a foundation for monitoring ecosystem health in the Bukit Doa Mahawu ecotourism area.